Dynamique de l'oxygène et l'activité microbienne dans les lacs de fonte du pergélisol subarctique - Deshpande, Bethany (Université Laval, 2016)
Thermokarst lakes (shallow lakes caused by the thawing and collapse of ice-rich permafrost) are a unique type of aquatic ecosystem, and are known to be strong emitters of greenhouse gases into the atmosphere. They are highly abundant and experiencing rapid changes in subarctic Quebec, becoming larger and deeper in some regions. The objective of this study was to provide an improved understanding of oxygen dynamics in thermokarst lakes, while also evaluating the controlling factors for these variations and the potential future changes in oxygenation in this globally important class of freshwater ecosystems. A wide range of techniques was employed throughout this study, including a combination of in situ, laboratory, and modelling approaches. Autonomous oxygen, conductivity and temperature sensors were employed from summer 2012 to 2015, providing continuous measurements at 10- to 60-minute intervals throughout the study. Laboratory measurements included bacterial respiration and production rates, geochemical lake variables, and an investigation of bacterial community size-fractions. Lake temperature and oxygen concentrations were modelled in one thermokarst peatland lake from the recent past (1971) to the future climate (2095), employing a moderate (RCP 4.5) and more extreme (RCP 8.5) climate-warming scenario. The results of this study revealed that anoxic conditions are prevalent in many thermokarst lakes throughout much of the year. High concentrations of ions accumulate throughout winter due to ice formation at the surface (cryoconcentration) and from ions released associated with hypolimnetic respiratory activity. The strong ion gradient resulted in a combined temperature- and salinity-based density gradient throughout winter. Some lakes were dimictic, mixing twice a year, while others only mixed completely once in fall or never throughout the annual cycle. There were abundant and highly active bacterial populations, with respiratory rates comparable to those observed in meso- or eutrophic systems of the ...